The economic burden of overactive bladder (OAB) and its effects on the costs associated with other chronic, age‐related comorbidities in the United States. Issue 5 (21st February 2018) - Durden, Emily; Walker, David; Gray, Stephani; Fowler, Robert; Juneau, Paul; Gooch, Katherine
Abstract : Aims: The prevalence of OAB increases with age and is associated with several chronic comorbidities. However, the impact of OAB on the healthcare costs of patients with such comorbidities is not well‐understood. This study aimed to quantify the impact of OAB on healthcare costs and assess the potential moderating effects of OAB on the costs of patients with chronic comorbidities. Methods: Adults with evidence of OAB/OAB‐related therapy between 1/1/2008‐12/31/2013 were identified from two large, administrative claims databases. Per‐patient‐per‐month (PPPM) expenditures for OAB cases were estimated and compared to those of propensity score‐matched subjects without OAB. Costs were modeled using ordinary least squares regression including main effects and interactions of chronic depression, dementia, diabetes, hypertension, and osteoporosis with OAB. Values for the comparisons were calculated on the original dollar scale using smearing estimators. Results: A total of 110 059 pairs of OAB cases and matched non‐OAB controls were identified. The mean, multivariable‐adjusted, PPPM all‐cause costs of OAB cases from the model without interactions were $3003, compared to $1123 for matched controls ( P  < 0.0001). In the model assessing the interactions of chronic comorbidities with OAB, those OAB patients with comorbid depression, dementia, diabetes, hypertension, and osteoporosis incurred significantly higher costs than controls with these comorbidities. The synergistic effect of these interactions was estimated to be $95‐$574 PPPM. Conclusions: Within this US‐based population, the healthcare costs of OAB patients were more than 2.5 times those of similar patients without OAB. Additionally, patients with OAB and chronic, age‐related comorbidities incurred higher healthcare costs than non‐OAB controls with the same comorbidities.